2013
DOI: 10.4081/itjm.2013.s8.65
|View full text |Cite
|
Sign up to set email alerts
|

New anticoagulant drugs versus warfarin in atrial fibrillation: economic evaluation and cost-effectiveness analysis

Abstract: Health care resources available for medical procedures, including pharmaceuticals, are limited worldwide. Health economic evidence is now accepted as an essential component of health technology appraisal, realizing the importance of value for money considerations for a more efficient (cost-effective) prescribing. Regulatory agencies in more and more countries perform economic evaluation and cost-effectiveness analysis in order to decide about reimbursement of a new and almost always more expensive drug. Pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Direct oral anticoagulants (DOACs) became available as an alternative to warfarin during the past decade. Clinical trials have shown that the efficacy of DOACs is similar to warfarin (Connolly et al, 2009;Granger et al, 2011;Patel et al, 2011), while the advantage is that these drugs prevent thromboembolic complications without regular monitoring (Silingardi, 2013). DOACs have significantly less adverse interaction with food and drugs than warfarin, which allows fixed dosing (Testa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Direct oral anticoagulants (DOACs) became available as an alternative to warfarin during the past decade. Clinical trials have shown that the efficacy of DOACs is similar to warfarin (Connolly et al, 2009;Granger et al, 2011;Patel et al, 2011), while the advantage is that these drugs prevent thromboembolic complications without regular monitoring (Silingardi, 2013). DOACs have significantly less adverse interaction with food and drugs than warfarin, which allows fixed dosing (Testa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%